The Comparison of Resistance and Endurance Exercises on Fatigue Severity and Balance in Women with Multiple Sclerosis - Ahmad Ebrahimi Atri; Maryam Sokhangoi; Fateme Sarvari (Sport Sciences and Health Research)
Multiple sclerosis is a chronic progressive disease of central nervous system with disabling signs and symptoms which cause severe disorders and damaging effects on daily performance, business and social activities and the patients feel general well-being; therefore, non – drug treatment is recommended to control symptoms of MS. The aim of this study was to compare the effects of the endurance and resistance exercises on fatigue severity and balance in women with multiple sclerosis. This study was a semi-experimental study and the goal was applied. 20 women with MS (mean age of 30.9+6.95 years) with expanded disability status scale of disease (EDSS)≤4 participated in this study and. were randomly assigned to two groups: resistance exercise group (n=10) and endurance exercise group (n=10). Training protocol lasted 8 weeks, two sessions per week (16 sessions) and each session consisted of three stages: warm-up, exercise, cool-down. The severity of fatigue and balance was measured before and after the protocol by FSS scale and lateral reach test (to the right and left side). The results showed a significant difference between the severity of fatigue and balance scores in patients with MS before and after the training period (P<0.05), but there was no significant difference between the two group (P>0.05). It can be concluded that the strength and endurance exercises can improve fatigue severity and balance in patients with MS. On the other hand, insignificant difference between fatigue severity and balance scores between the two groups after training shows the same effect of both types of exercises on the improvement fatigue severity and balance in patients with multiple sclerosis.